Development of Two Distinct Dendritic-Like APCs in the Context of Splenic Stroma - Periasamy, Pravin; Petvises, Sawang; O'Neill, Helen (Frontiers in Immunology, 2013)
Murine splenic stroma has been found to provide an in vitro niche for hematopoiesis of dendritic-like APCs (APC). Two distinct cell types have been characterised. The novel ‘L-DC’ subset, has cross presenting capacity leading to activation of CD8+ T cells, but do not activate CD4+ T cells consistent with their CD11cloCD11bhiMHC-II- phenotype. For L-DC, an equivalent tissue-specific APC has been found only in spleen. A second population of CD11chiCD11bloMHC-II+ cells resembling conventional dendritic cells (cDC) can activate both CD4 and CD8 T cells. Production of L-DC but not cDC-like cells is now shown to be dependent on contact between the L-DC progenitor and stroma such that the presence of a Transwell membrane can prevent L-DC development. Since L-DC can be produced continuously in vitro in stromal co-cultures overlaid with bone marrow (BM) progenitors, it was hypothesised that L-DC progenitors are self-renewing. The L-DC progenitor is shown here to be defined by the Flt3-c-kit+Lin-Sca-1+ (F-KLS) subset of adult BM which contains primitive HSC. Since the less primitive F+KLS HSC subset also contains L-DC progenitors, Flt3 does not appear to be a defining marker for this progenitor. Precursors of the cDC-like subset are found only within the F+KLS subset and seed production of a transient population of APC. All data identify differentiation of L-DC from HSC, and of cDC-like cells from DC precursors, which occurs independently of inflammatory signals and is dependent on a splenic stromal microenvironment.